Medical 3D printing - the future is here - Kamil Szpiech; Konrad Gładysz; Patrycja Gierszon; Adrian Kuś; Małgorzata Szypłowska Szypłowska; Małgorzata Neścior (Kazimierz Wielki University, 2019)
Introduction: Continuous advances in polymer development and thriving 3D printing methods enable us to reproduce components with exceptional print precision and ensure material biocompatibility under sterile conditions. All this comes down to the fact that the resulting prints better fulfill their roles in the world of medicine and enable patients to recover faster. This precision translates into the main advantage of 3D printing, i.e. personalisation of models with perfectly reproduced structures of a given patient based on CT or MRI tests. At the same time, these prints can be used for didactic purposes by medical students from the very beginning of their professional career, which in the future will make it much easier to perform difficult and complicated operations. Aim of the study: Presentation of the application and positive aspects of 3D printing in medicine. Summary: 3D printing is a permanent feature on the pages of modern medicine. Thanks to it we get to know the personalized morphology of given structures, we more accurately prepare ourselves for the procedure and more often prevent probable complications, and our medical staff receives another dose of knowledge, which they translate into the profession. Conclusions: Training on perfectly reproduced copies printed in 3D can certainly attest to the high qualifications of specialist doctors. The use of widely understood 3D printing technique in medicine is slowly becoming commonplace.